The interactive fuzzy semigroup (RIC,+1/2) and its algebraic structure properties - de Andrade, Allan Edley Ramos; Wasques, Vinícius Francisco [UNESP] (Elsevier, 2024)
This paper studies algebraic properties of fuzzy numbers under a specific arithmetic operation denoted by +1/2. Specifically, this article establishes a new semigroup based on this sum and explores its algebraic properties, as well as homomorphisms between its subsemigroups. Some examples are provided in order to illustrate the results provided here.
Keywords: Fuzzy algebra; Interactive fuzzy arithmetic; Interactive fuzzy numbers; Semigroups